The impact of tacrolimus levels on acute GVHD and transplant outcomes in haploidentical hematopoietic stem cell transplantation: A retrospective analysis - Alexander Nikoloudis; Veronika Buxhofer-Ausch; Ameya Kunte; Christina Groiss; Lorenz Mair; Christoph Aichinger; Michaela Binder; Petra Hasengruber; Emine Kaynak; Dagmar Wipplinger; Robert Milanov; Irene Strassl; et al. (Cell Transplantation)
The impact of early tacrolimus (TAC) blood levels on acute graft-versus-host disease (aGVHD) and transplant outcomes in adults undergoing haploidentical hematopoietic stem cell transplantation (haplo-HSCT) with posttransplant cyclophosphamide (PTCy) is incompletely investigated. We retrospectively analyzed 161 T-cell–replete haplo-HSCT with PTCy, TAC, and mycophenolate-mofetil. TAC trough levels from weeks 1–2 (w1/2) and weeks 3–4 (w3/4) posttransplant were categorized as “Low” or “High” using a threshold of 10 ng/ml. Outcomes assessed included grade III–IV acute graft-versus-host-disease (aGVHD), nonrelapse mortality (NRM), relapse, and overall survival (OS). Multivariate analyses controlled for relevant patient and transplant factors. Higher w1/2 TAC (≥10 ng/ml) in weeks 1–2 had no association with aGVHD III/IV (35% vs. 35%, P = 0.71). Higher TAC levels during w3/4 were associated with a trend toward decreased aGVHD III–IV incidence (8% vs. 20%; P = 0.09). Multivariate analysis confirmed w3/4 TAC levels as protective against aGVHD III/IV (sub-Hazard Ratio [sHR] = 0.83, 95% CI: 0.70–0.98, P = 0.03) and NRM (sHR = 0.82, 95% CI: 0.71–0.95, P = 0.01), while w1/2 TAC levels had no significant impact on the above outcomes. TAC levels did not significantly impact OS or relapse. We conclude that following PTCy-based haplo-HSCT, higher TAC levels during weeks 3–4 may decrease aGVHD and NRM.